Constitutional legitimacy of the interim government: Analysis on Bangladesh Perspective - Sayed Mohammad Abu Daud (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2024)
Bangladesh now has an interim government, which acts as a transitional government between the old and new regimes, with the responsibility of maintaining stability and laying the groundwork for a more permanent solution. Imagine a country on the verge of collapse. A valid revolution was successful. A fascist prime minister has resigned and is running away, and it has left the country in disarray. What happens next? Who takes control? This is where the fascinating concept of an interim government steps onto the stage. The issue of constitutional legitimacy surrounding an interim government in Bangladesh is a pivotal subject that impacts the country’s democratic processes. This paper analyzes the constitutional legitimacy of an interim government in Bangladesh, focusing on historical context, legal principles, and the ongoing scenario after the July revolution.